2020
DOI: 10.1002/pld3.211
|View full text |Cite
|
Sign up to set email alerts
|

Introducing plant biology graduate students to a culture of mental well‐being

Abstract: Currently, an estimated 20%–40% of graduate students have depression and anxiety. In addition, more than half report experiencing high chronic stress. Thus, organizations such as the Plant Science Research Network have highlighted the need to prioritize trainee well‐being. This has led to a search for strategies to introduce this cultural change into scientific training. However, for faculty who do not have experience with this topic area, there are few readily available resources from which to draw. In this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…While this study included two intervention groups exposed to the same intervention, it did not include a control group. The remaining four studies found no significant changes (Damião Neto, et al, 2020;Dewa, et al, 2020;Gan, et al, 2022;Johnson, et al, 2019).…”
Section: Curricular Infusionmentioning
confidence: 87%
See 3 more Smart Citations
“…While this study included two intervention groups exposed to the same intervention, it did not include a control group. The remaining four studies found no significant changes (Damião Neto, et al, 2020;Dewa, et al, 2020;Gan, et al, 2022;Johnson, et al, 2019).…”
Section: Curricular Infusionmentioning
confidence: 87%
“…The 18 studies included one randomised controlled trial (RCT; Damião Neto, et al, 2020), five quasi-experimental (Ahmad, et al, 2017;Dyrbye, et al, 2017;Maynor, et al, 2022;Mc Sharry & Timmins, 2016;Poole, et al, 2018), three qualitative (Agnew, et al, 2019;Bosse, et al, 2021;McArthur, et al, 2021), and nine mixed-methods (Culver, et al, 2021;Dewa, et al, 2020;Gan, et al, 2022;Johnson, et al, 2019;Litchke, et al, 2020;Pilato, et al, 2022;Poole, et al, 2017;Wang & Du, 2020;Whiteside, et al, 2017).…”
Section: Study Types and Designsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study by Dewa et al -integrating a sevenlesson mental wellbeing course in the graduate plant biology program -showed behavioral changes with regard to positive wellbeing in their students as well. [47] Acquiring practical skills and making behavioral changes positively in uences wellbeing and may also stimulate an attitude of lifelong learning that is necessary for every medical professional. [29,48]…”
Section: Analysis Of the Narrative Individual Answersmentioning
confidence: 99%